Ulul Albāb dalam Al-Qurán dan Relasinya dengan Perubahan Sosial - Adi Tahir Nugraha (Jurnal Iman dan Spiritualitas, 2021)
Ulul albab is usually used as an academic term by those who use it as a motto or philosophy of movement both personally and institutionally. This term is repeated 16 times in the Qur'an, indicating that there is something special in it. This also shows how crucial ulul albab is in human life. Therefore, the study of ulul albab invites more profound attention, whether it is appropriate that ulul albab is categorized only to describe an intellectual character or not. This study uses a maudhuí interpretation approach, a thematic interpretation approach compiling verses with the same theme for further interpretation. Furthermore, this research raises a fundamental problem to answer how Al-Qurán describes the ulul albab and how is the relevance of the understanding of ulul albab with life. Based on the formulation of the problem, several answers were found that the ulul albab is the one who has a mind and uses it in its place. Humans who characterize the depth of thought, dhikr, and have high moral values. Another explanation is that ulul albab has the sharpness of reason and spiritual depth, whose belief is firm in exercising faith in Allah which is manifested in religious ritual activities in the aspect of worship and those who do not forget to pray to Allah. In another aspect, it is described as a person who thinks about the universe. It ends in the element of belief and commitment to always care for nature and the environment, and society.